Holland, Dickinson County - May, Matthew (Kansas State University, The Chapman Center for Rural Studies, 2012)
Families in Holland, Kansas, a Dickinson County town seven miles south of Abilene, sought to form a community that could provide a education for their children, respite from the continuous toil the soil required, and, eventually, a structure to create some economic security.
Matthew May, “Holland, Dickinson County,” Chapman Center Research Collections, accessed October 23, 2020, https://ccrsresearchcollections.omeka.net/items/show/145.
Keywords: Clem Bell; Creamery; Dairy; Dickinson County; Holland; Sue Bell